Models to define the stages of articular cartilage degradation in osteoarthritis development - Poulet, Blandine (Int J Exp Pathol, 2017)
Osteoarthritis (OA) is a common chronic disorder that affects an increasing number of the ageing population. Despite the prevalence, there are currently no therapies. Defining new therapies that target specific pathogenic phases of disease development relies on the effective separation of the different stages of OA. This manuscript reviews the tissues and models that are being used to separate these stages of disease, in particular initiation and early and late progression. These models include human tissues with known initiating factors, the use of anatomical locations with defined relationships to the primary cartilage lesion area, timing of OA development in well‐described animal models and the versatility of a non‐invasive model of murine knee joint trauma.